Relationship between methylation and colonic inflammation in inflammatory bowel disease - Lobatón, Triana (Baishideng Publishing Group Inc, 2014)
AIM: To investigate the relationship between the methylation status in the SLIT2 and TGFB2 promoters and colonic inflammation in inflammatory bowel disease patients. METHODS: We evaluated the methylation status of 2 genes (SLIT2 and TGFB2) in 226 biopsies taken from 62 colonoscopies of 38 patients (29 ulcerative colitis and 9 Crohn’s colitis) using methylation-specific melting curve analysis. The relationships between methylation status and clinical, biological, endoscopic and histological activities were evaluated. Twenty-three of the 38 patients had a second colonoscopy and were included in a longitudinal analysis. Numerical results were given as the means ± SD of the sample and range, except when specified. Student t analysis, U Mann Whitney and ANOVA factor were used to compare the means. Qualitative results were based on the χ(2) test. RESULTS: SLIT2 methylation was more frequent in samples with endoscopic activity than with endoscopic remission (55% vs 18%, P < 0.001). SLIT2 methylation was also higher in samples with acute inflammation (56.5%) than in samples with chronic (24%) or absent inflammation (15%) (P < 0.001). For TGFB2 methylation, the correlation was only significant with endoscopic activity. Methylation was higher in the distal colon for both genes (P < 0.001 for SLIT2 and P = 0.022 for TGFB2). In the multivariate analysis, only inflammation status (and not disease duration or extension) was independently associated with SLIT2 methylation [OR = 6.6 (95%CI: 1.65-27.36), P = 0.009]. In the longitudinal analysis, the maintenance of endoscopic remission was protective for methylation. CONCLUSION: Endoscopic and histological inflammation are predictive for SLIT2 methylation.